EVALUATION OF POLYHERBAL FORMULATION IN EXPERIMENTALLY INDUCED GASTRIC ULCERS IN RATS - Narendra R. Dighade , Shubhangee Tomar , Krupa Mansukhbhai Badava , Gracerity Nongrum , Alka Mishr , Farhad F Mehta , Sachin Dhull , Murali Krishna Kandukuri (South Eastern European Journal of Public Health, 2025)
A painful open break or rupture on the skin or mucous membrane that prevents the organ from performing its normal duties is called an ulcer. Due to the adverse effects of allopathic medications, ayurvedic preparations are in the lead. Previous research that shown that individual plants have antiulcer efficacy but that there was no polyherbal combination of them were used to construct this polyherbal combination. Thus, the goal of the current investigation was to assess the anti-ulcer effectiveness of a polyherbal preparation employing Wistar albino rats against stomach ulcers caused by ethanol and pylorus ligation. Rats were given polyherbal extract at 200 mg/kg and 400 mg/kg body weight, and the results were contrasted with those of omeprazole (10 mg/kg), a common medication. When compared to the disease control group animal, the extract significantly decreased the ulcer index at doses of 200 mg/kg (p˂0.05) and 400 mg/kg (p˂0.01) in the ethanol-induced ulcer model and 200 mg/kg (p˂0.05) and 400 mg/kg (p˂0.05) in the pylorus ligation model. Reduced gastric juice volume, ulcer protection percentage, ulcer index, and increased free acidity are indicators of antiulcer action. Due to the antioxidant, antisecretory, and cytoprotective properties of these plants, this polyherbal mixture exhibits antiulcer activity. We may therefore draw the conclusion that the polyherbal formulation exhibits strong antiulcer properties.